2017
DOI: 10.1155/2017/8127814
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Community Profile of the Gut Microbiota Differs between Hypercholesterolemic Subjects and Controls

Abstract: The role of gut microbiota in the development of metabolic illnesses has been abundantly demonstrated. Recent studies suggest that gut microbiota alterations may also be related to the development of hypercholesterolemia. Therefore, we aimed to assess differences in the gut bacterial community profiles between hypercholesterolemic subjects and controls. Thirty cases diagnosed with hypercholesterolemia and 27 normocholesterolemic controls were included. A fasting whole blood sample was obtained to determine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 32 publications
1
27
0
1
Order By: Relevance
“…In this study, Rebolledo et al analyzed the fasting whole blood lipid profile and bacterial community profiles by denaturing gradient gel electrophoresis. As expected, hypercholesterolemia subjects had higher levels of serum total cholesterol, triglycerides, and LDL-cholesterol than controls, while they harbored a lower richness and diversity of gut microbiota, thus proposing a potential role of the gut microbiota in the development of hypercholesterolemia [44]. Karlsson et al performed the metagenomic sequencing with fecal samples collected from 145 European women with normal, impaired, or diabetic glucose control, and reported a negative correlation between serum triglycerides and Clostridum, and a positive correlation between HDL and Clostridium [45].…”
Section: The Association Between the Gut Microbiome And Lipid Profilesupporting
confidence: 56%
See 1 more Smart Citation
“…In this study, Rebolledo et al analyzed the fasting whole blood lipid profile and bacterial community profiles by denaturing gradient gel electrophoresis. As expected, hypercholesterolemia subjects had higher levels of serum total cholesterol, triglycerides, and LDL-cholesterol than controls, while they harbored a lower richness and diversity of gut microbiota, thus proposing a potential role of the gut microbiota in the development of hypercholesterolemia [44]. Karlsson et al performed the metagenomic sequencing with fecal samples collected from 145 European women with normal, impaired, or diabetic glucose control, and reported a negative correlation between serum triglycerides and Clostridum, and a positive correlation between HDL and Clostridium [45].…”
Section: The Association Between the Gut Microbiome And Lipid Profilesupporting
confidence: 56%
“…In addition, a study of 30 hypercholesterolemia individuals and 27 healthy controls reported differences in commensal bacterial profiles between hypercholesterolemic subjects and controls [44]. In this study, Rebolledo et al analyzed the fasting whole blood lipid profile and bacterial community profiles by denaturing gradient gel electrophoresis.…”
Section: The Association Between the Gut Microbiome And Lipid Profilementioning
confidence: 95%
“…Additionally, the profile of the microorganisms that are present is different, which suggests that IM possibly play a role in development of hypercholesterolemia. 7 Manipulation of the IM with probiotics results in several benefits for the host. 8,9 Probiotics are already in use in human medicine, both for disease prevention and for treatment, by controlling the IM.…”
Section: Introductionmentioning
confidence: 99%
“…between patients with diabetes and healthy individuals. It is previously reported that total cholesterol and low-density lipoprotein cholesterol reduction are associated with dairy products enriched with Enterococcus faecium in participant having a normal lipid profile and participant with medium to moderate hypercholesterolemia [38].…”
Section: Discussionmentioning
confidence: 96%